THE EFFECTIVENESS OF USING JIGSAW AND SQ3R TECHNIQUE IN INSTRUCTION TOWARD THE STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT THE EIGHT GRADE OF JUNIOR HIGH SCHOOL STATE 8 METRO ACADEMIC YEAR 2011/2012 - Tri Yuliani (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2012)
This undergraduate thesis analyzes about students’ reading comprehension of narrative text. There are many kinds of techniques that can be used in instruction of reading such as jigsaw and SQ3R. The problem formulation in this research are: (1) Is there any significant difference students’ reading comprehension between using jigsaw and SQ3R. (2) Which one is more effective between using jigsaw and SQ3R technique in reading comprehension. The objectives of this research are (1) To know the difference students’ reading comprehension between using jigsaw and SQ3R. (2) To know which one is more effective tehcnique between using jigsaw and SQ3R toward reading comprehension.Research design of this research is experimental group. The kind of design is control group pre-test and post-test design. The research is conducted at the eight grade of SMP N 8 Metro academic year 2011/ 2012. The researcher takes 48 students from total population as the sample, 24 students as experiment class and 24 students as control class that matching based on students’ initial capability. There are two instruments in this research, the first one is Pre-Test and the second is Post-test.The researcher uses ttest formula. The researcher get the result of ttestis 3,17 and ttableis 2,70 (on criterion 1) and 2,02 (on criterion 2). It means that thit> ttable. So, there is any difference reading comprehension of narrative text using Jigsaw and SQ3R. Jigsaw technique is more effective technique than SQ3R technique toward reading comprehension of narrative text at Eight grade of Junior High School State 8 Metro academic year 2011/ 2012. The researcher expects English teacher use Jigsaw technique in reading instruction.